POTENTIAL OF MALTODEXTRIN CAPSULES OF AVOCADO LEAF EXTRACT (PERSEA AMERICANA MILL.) AS ANTIOXIDANT PRODUCTS - Rahman, Nurdin; Mulyani, Sri; Fuadi, Nurul; Aiman, Ummu; Ariani; Bohari (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyze the characteristics of maltodextrin capsules of avocado leaf extract. It was conducted in the Analytical Chemistry Laboratory of the Mathematics and Science Faculty of Tadulako University. The research variables are antioxidant power, anthocyanin content, phenolic content, tannin content, water content, and toxicity test in mice with various doses. It was found that the % inhibition of avocado leaf extract maltodextrin capsules increases with the increasing concentrations of 33.662% - 51.996% with the IC50 value of 78.732. The phenolic, tannin and antiocyanin contents in maltodextrin capsules of avocado leaf extract on average are high by 39.94 mg/dL (Phenol), 59.54 mg/dL (Tannin), 0.0004 g/l (Anthocyanin) and low water solubility of 8.219%. The results of the toxicity test show that the administration of the avocado leaf extract maltodextrin capsules observed for 24 hours did not obtain data on the death of the test animals. It is concluded that the avocado leaf extract maltodextrin capsule has high antioxidant power with high anthocyanin, phenolic and tannin contents that can be used as a product rich in antioxidant content.